1982
DOI: 10.1080/09553008214551241
|View full text |Cite
|
Sign up to set email alerts
|

DNA Double Strand Breaks in Ehrlich Ascites Tumour Cells at Low Doses of X-rays. II. Can Cell Death be Attributed to Double Strand Breaks?

Abstract: The induction and repair of DNA double strand breaks (dsb) in early stationary Ehrlich ascites tumour cells by X-rays was determined using an improved sedimentation technique in neutral sucrose gradients. The disappearance of dsb was followed during post-irradiation incubation of the cells and was interpreted as dsb repair. Kinetics were approximated by exponential functions with time constants of t37 = 3.0 +/- 0.7 hours ('conditioned' medium) and t37 = 2.0 +/- 0.5 hours (growth medium). Maximal repair was rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…(Table 2). This value confirmed our previous results El-Awady et al, 2001) and also agreed well with other data (range 8 -15  10 À12 dsb/Gy/Da) based on PFGE, from which a number of dsb can be calculated when it is combined with either 125 I-decay, analysis of fragment size distribution after high doses, or restriction digest (Blöcher and Pohlit, 1982;Iliakis et al, 1991a, b;Lawrence et al, 1993;Cedervall et al, 1994Cedervall et al, , 1995Löbrich et al, 1994a, b;Löbrich, 1999, 2003). Only, Ruiz de Almodovar et al (1994) found a much higher induction frequency of about 66 dsb  10 À12 /Gy/Da.…”
Section: Number Of Induced Dsbsupporting
confidence: 92%
“…(Table 2). This value confirmed our previous results El-Awady et al, 2001) and also agreed well with other data (range 8 -15  10 À12 dsb/Gy/Da) based on PFGE, from which a number of dsb can be calculated when it is combined with either 125 I-decay, analysis of fragment size distribution after high doses, or restriction digest (Blöcher and Pohlit, 1982;Iliakis et al, 1991a, b;Lawrence et al, 1993;Cedervall et al, 1994Cedervall et al, , 1995Löbrich et al, 1994a, b;Löbrich, 1999, 2003). Only, Ruiz de Almodovar et al (1994) found a much higher induction frequency of about 66 dsb  10 À12 /Gy/Da.…”
Section: Number Of Induced Dsbsupporting
confidence: 92%
“…1 It is not necessary to destroy a large portion of the genome to kill a cell; one unrepaired DNA double-strand break is sufficient to kill a cell and reflects apoptosis. 42,43 Additionally, vinculin defines costameres on the plasma membrane, and loss of sarcolemmal lining and myofibrillar structures does not leave costameres intact. Therefore, vinculin is a reliable marker for the identification of the integrity or discontinuity of the surface membrane.…”
Section: Efficiency Of Light (Lm) Confocal (Cm) and Electron (Em) Mmentioning
confidence: 99%
“…6), in the observed modulation of the DNA elution dose response curves at pH values closer to neutrality . High pH during lysis was used in centrifugation (Bloecher 1982) and in gel electrophoresis (Schwarz and Cantor 1984) techniques measuring induction of DNA dsb . In summary the results presented indicate that the DNA elution dose response observed with CHO cells under non-unwinding conditions, can be altered by the selection of the detergent used as well as by the temperature during lysis .…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using nondenaturing filter elution and neutral sucrose density sedimentation suggested that the shoulder observed in the DNA elution dose response curve may be due to a DNA-protein complex that is resistant to detergents and proteolytic enzymes (under the conditions used) and sensitive to radiation ). The fact that in the non-unwinding DNA elution technique lysis conditions are usually used which in other assay systems (velocity sedimentation, gel electrophoresis) have been proven inadequate in removing DNA bound proteins (Bloecher 1981, 1982, Bloecher and Pohlit 1982, Bloecher et al . 1983, Schwarz and Cantor 1984, rendered indirect support to this assumption .…”
Section: Introductionmentioning
confidence: 98%